2009
DOI: 10.1002/mus.21396
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of peripheral neuropathy in Machado–Joseph disease

Abstract: Peripheral neuropathy (PN) has long been recognized in Machado-Joseph disease (MJD), but its natural history is an unsettled issue. Therefore, we prospectively assessed 40 with MJD for 13 months with nerve conduction (NC) studies and the revised total neuropathy score (TNSr) to study the progression of PN. There was no significant change in the TNSr score over the follow-up period. In contrast, the average sural sensory nerve action potential (SNAP) amplitude decreased significantly over the same interval from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
6
17
0
Order By: Relevance
“…We found no correlation between CAG repeat length and neuropathy or TNSc scores, which is in line with previous data [11,14,15]. Conversely, there was a significant positive correlation between the presence of neuropathy and the age of the patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found no correlation between CAG repeat length and neuropathy or TNSc scores, which is in line with previous data [11,14,15]. Conversely, there was a significant positive correlation between the presence of neuropathy and the age of the patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our neurophysiological studies showed that neuronopathy was present in 81.8% of MJD patients with neuropathy, which is in line with that reported by França et al [15] and higher than other data [14]. Considering that neuronopathy is the main pattern of nerve involvement in MJD patients, it suggests that damage to neuronal cell bodies is a major factor leading to peripheral neuropathy in these patients rather than axonal damage that would lead to length-dependent distal neuropathy [3,4,14,19].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Peripheral neuropathy has long been recognized in SCA3/MJD patients [15]. In our study, among 26 patients studied, 9 (34%) had neuropathy.…”
Section: Discussionmentioning
confidence: 78%
“…Extrapyramidal signs comprise dystonic movements, chorea and parkinsonian features. Later, evidence of progressive symptomatic peripheral polyneuropathy with impairment in sensory nerve action potentials can occur [2]. Late in the disease course, patients are confined to a wheelchair, and later become bedridden.…”
Section: Introductionmentioning
confidence: 99%